Thriving on chaos: Proactive detection of command and control domains in internet of things‐scale botnets using DRIFT. Issue 4 (29th August 2018) - Spaulding, Jeffrey; Park, Jeman; Kim, Joongheon; Nyang, DaeHun; Mohaisen, Aziz
Abstract: In this paper, we introduce DRIFT, a system for detecting command and control (C2) domain names in Internet of Things–scale botnets. Using an intrinsic feature of malicious domain name queries prior to their registration (perhaps due to clock drift), we devise a difference‐based lightweight feature for malicious C2 domain name detection. Using NXDomain query and response of a popular malware, we establish the effectiveness of our detector with 99% accuracy and as early as more than 48 hours before they are registered. Our technique serves as a tool of detection where other techniques relying on entropy or domain generating algorithms reversing are impractical. Abstract : We introduce DRIFT, a system for detecting command and control (C2) domain names in Internet of Things (IoT)–scale botnets. Using an intrinsic feature of malicious domain name queries prior to their registration (perhaps due to clock drift), we devise a difference‐based lightweight feature for malicious C2 domain name detection. Using NXDomain query and response of a popular malware, we establish the effectiveness of our detector with 99% accuracy and as early as more than 48 hours before they are registered.